CORNEAL COMPLICATIONS AND VISUAL IMPAIRMENT IN VERNAL KERATOCONJUNCTIVITIS PATIENTS - Arif, Abdus Salam; Aaqil, Bushra; Siddiqui, Afsheen; Nazneen, Zainab; Farooq, Umer (Journal of Ayub Medical College Abbottabad, 2017)
Background: Vernal kerato-conjunctivitis (VKC) is an infrequent but serious form of allergic conjunctivitis common in warm and humid areas where air is rich in allergens. It affects both eyes asymmetrically. Although VKC is a self-limiting disease but visions affecting corneal complications influence the quality of life in school children. The aim of this study was to list the corneal complications due to this condition and to find out the extent of visual impairment among VKC patients. Methods: This cross-sectional study was conducted in the department of Ophthalmology, Benazir Bhutto Shaheed Hospital on 290 eyes of diagnosed cases of VKC. The diagnosis of VKC was made on the basis of history and examination. Visual acuity was recorded using Snellen’s notation and visual impairment was classified according to World Health Organization classification for visual disabilities. Results: The mean age of presentation was 10.83±6.13 years. There were 207 (71.4%) males and 83 (28.6%) females. Corneal scarring was observed in 59 (20.3%) eyes. Keratoconus was found to be in 17 (5.9%) eyes. Shield ulcer was detected in 09 (3.1%) eyes while 07 (2.4%) eyes had corneal neovascularization. Majority of the patients with visual loss had corneal scarring and the complication that led to severe visual loss in most of the eyes was Keratoconus. Conclusion: Vernal kerato-conjunctivitis in the presence of corneal complications is a sight threatening disease and can lead to severe visual impairment. Keywords: Vernal kerato-conjunctivitis; Corneal complications; Visual impairment